Gastrointestinal forms of allergic diseases, which are accompanied by hemorrhagic colitis syndrome, in young children - O.Yu. Belousova (Zaslavsky O.Yu., 2021)
The article discusses the problem of the spread of allergic diseases among young children. Infant gastrointestinal disorders, caused by a range of allergens, but most often by exposure to cow's milk proteins, are one of the most frequent and at the same time most difficult clinical problems for the pediatrician. Particular attention in this article is paid to the so-called non-IgE-mediated forms of allergy to cow's milk proteins, that is, to such forms of allergy in which the epithelium of the child's digestive tract is damaged in the absence of any skin and/or respiratory manifestations. Some of these forms of allergy are accompanied by hemorrhagic colitis syndrome, which is an alarming signal, or the so-called "red flag", for pediatricians and family doctors, and which requires attention, differential diagnosis and competent adequate therapy. An essential (and in some cases the only) component of such therapy is elimination of the allergen from the diet of a child or a nursing mother and/or the use of a breast milk substitute that does not contain a causative allergen. To this end, according to the guidelines of the European Academy of Allergology and Clinical Immunology, it is proposed to use in formula-fed children either extensively hydrolyzed formulas as the first choice formulas, or amino acid formulas, but only with intolerance of extensively hydrolyzed formulas.